The role of energy transition in anticipating the impacts of climate change - Nugroho, Handi Wilujeng (Interaction, Community Engagement, and Social Environment, 2025)
Background: Climate change has emerged as one of the most pressing global challenges in the 21st century, with Indonesia an archipelagic and tropical nation being particularly susceptible to its consequences. Despite its enormous renewable energy (RE) potential of over 3,600 GW, Indonesia remains heavily dependent on fossil fuels, especially coal, which contributes significantly to greenhouse gas emissions and environmental damage. This study aims to analyze Indonesia’s energy transition strategy through the lens of climate justice, emphasizing the importance of an inclusive and equitable transformation. Previous research has underscored the critical role of distributive, procedural, and recognition justice in enabling fair energy transitions. Methods: This study applies a qualitative-descriptive approach using literature-based research. It draws on national policies, legal documents, academic journals, and global reports to evaluate Indonesia's energy transition framework. The analysis is grounded in the energy justice framework, which examines equity in energy distribution (distributive), inclusiveness in decision-making (procedural), and acknowledgment of vulnerable groups (recognition). Findings: The results show that Indonesia’s energy transition efforts are evolving but face significant challenges, including regulatory uncertainty, limited investment, and institutional rigidity. Although policy measures like the Just Energy Transition Partnership (JETP) and Presidential Regulation No. 112/2022 represent a shift towards a cleaner model, actual renewable energy installed capacity remains under 1%. Structural barriers such as fossil fuel subsidies and bureaucratic delays hamper progress. Integrating justice principles can enhance effectiveness by ensuring fair access, local empowerment, and participatory policy design. Conclusion: Indonesia’s energy transition is a vital strategy to mitigate climate change but must be rooted in justice to ensure inclusivity and sustainability. Strong policy coordination, stakeholder collaboration, and innovative financing mechanisms are necessary for success. Novelty/Originality of this article: This study offers a novel contribution by placing energy justice at the center of the analytical framework, unlike most existing literature on JETP or energy policy in Southeast Asia, which primarily focuses on financing mechanisms, technical pathways, or climate mitigation goals. By integrating environmental, socio-political, and governance dimensions, this research provides a comprehensive, justice-oriented evaluation of energy transitions, particularly relevant for developing countries where equity, participation, and local impact are often underexplored.